2014
DOI: 10.4037/ajcc2015102
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Colonization and Lower Respiratory Tract Infections with Methicillin-Resistant Staphylococcus aureus

Abstract: Background Methicillin-resistant Staphylococcus aureus is a cause of lower respiratory tract infections, particularly health care-and ventilator-associated pneumonia. Although many health systems use nasal screening for this microorganism for infection control, correlation between nasal carriage of the organism and development of infections due to it is not clear. Methods Records of patients admitted to medical intensive care between January 1, 2011, and December 31, 2012, were reviewed retrospectively. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
46
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 19 publications
5
46
2
1
Order By: Relevance
“…Unfortunately, there were too few individual endotracheal tube aspirate, sputum, and BAL samples to analyze. However, studies including respiratory samples 15,17,18 have reported sensitivity and specificity similar to those found in the current study.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…Unfortunately, there were too few individual endotracheal tube aspirate, sputum, and BAL samples to analyze. However, studies including respiratory samples 15,17,18 have reported sensitivity and specificity similar to those found in the current study.…”
Section: Discussioncontrasting
confidence: 49%
“…Reported values for sensitivity and specificity of MRSA nasal-swab screening alone for predicting MRSA infection have ranged from 50.0% to 88.0% and from 83.0% to 100.0%, respectively. [15][16][17][18][19][20] The comparability of these results is limited by the different nasal- swab assays used at each site. Many studies used polymerase chain reaction, which has been shown to increase sensitivity 22 relative to the chromogenic medium used at the current study site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies have consistently shown that MRSA nasal colonization has a high negative predictive value (Ͼ94%) for MRSA recovered from lower respiratory sources, suggesting that the absence of MRSA in the nares can be used to predict the absence of MRSA in lower respiratory tract cultures (10)(11)(12)(13). A prior retrospective study from our group demonstrated that MRSA nasal culture screening had a 98.5% negative predictive value for MRSA lower respiratory tract cultures.…”
mentioning
confidence: 90%